Microsite-Based E-Learning as an Adaptive Pedagogical Tool: Enhancing Student Mastery of Rukhsah Concepts - Pratama, Farandika Nanda; Nusaibah, Nusaibah; Arliansyah, Ihsanul Hudiya (Jurnal Pendidikan Progresif, 2025)
Microsite-Based E-Learning as an Adaptive Pedagogical Tool: Enhancing Student Mastery of Rukhsah Concepts. Objective: Learning activities during the day and the insufficiency of the media used are obstacles for Islamic Religious Education (PAI) educators at SMP 1 Kudus, leading to low student attention and affecting students’ mastery of the learning material. This article presents a novelty: the development of e-learning media based on Microsite S.Id. as an innovative, interactive, and aligned solution with the Merdeka Curriculum. Methods: The purpose of this article is to describe the development process, the media's feasibility, and its potential to enhance students’ mastery of the Rukhsah concept. This research utilized the R&D method with the ADDIE model, involving 27 seventh-grade students at SMP 1 Kudus, Indonesia, and experts as validators. Data collection techniques included tests (pre-test and post-test) and non-tests (questionnaires, observations, interviews, and documentation). Findings: The media is classified as “Very Feasible” across the aspects of materials, media, teaching modules, and assessment. The results of concept mastery tests through the Wilcoxon Test showed a significance value of 0.000 (<0.05), along with an N-Gain Score of 0.8793 and an N-Gain Percent of 87.93%, which are categorized as “High” and “Very Effective." Conclusion: This article indicates that the use of e-learning media has the potential to improve students’ mastery of concepts and can be recommended as an adaptive alternative to make Islamic Education learning more enjoyable, especially during less conducive learning times, such as during the day. This article also recommends the use of digital-based media in other studies and suggests further research with a broader range of materials and education levels. Keywords: e-learning media, merdeka curriculum, microsite S.Id., concept mastery, rukhsah.